2012
DOI: 10.1007/s10495-011-0695-9
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: ICB3E induces iNOS expression by ROS-dependent JNK and ERK activation for apoptosis of leukemic cells

Abstract: The role of c-Jun N terminal Kinase (JNK) has been well documented in various cellular stresses where it leads to cell death. Similarly, extracellular signal-regulated kinase (ERK) which was identified as a signalling molecule for survival pathway has been shown recently to be involved in apoptosis also. Recently we reported that ICB3E, a synthetic analogue of Piper betle leaf-derived apoptosis-inducing agent hydroxychavicol (HCH), possesses anti-chronic myeloid leukemia (CML) acitivity in vitro and in vivo wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 55 publications
2
14
0
Order By: Relevance
“…Numerous studies indicated that ERK1/2 and JUK could be activated by many environmental stressors or chemical agents via induction of oxidative stress, but this phenomenon was inhibited by treatment with antioxidants Geng et al, 2014;Wang et al, 2014;Zhang et al, 2012). Also, oxidative stress could increase the protein or mRNA levels of MAPKs (Biswas et al, 2012;Liu et al, 2012;Liu et al, 2013). Our study showed that exposure to nitrite increased the mRNA levels of JUK1, implying that the JUK signaling pathways likely played a role in the damage of the turbot gill or branchial cells after nitrite exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies indicated that ERK1/2 and JUK could be activated by many environmental stressors or chemical agents via induction of oxidative stress, but this phenomenon was inhibited by treatment with antioxidants Geng et al, 2014;Wang et al, 2014;Zhang et al, 2012). Also, oxidative stress could increase the protein or mRNA levels of MAPKs (Biswas et al, 2012;Liu et al, 2012;Liu et al, 2013). Our study showed that exposure to nitrite increased the mRNA levels of JUK1, implying that the JUK signaling pathways likely played a role in the damage of the turbot gill or branchial cells after nitrite exposure.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 While ERK signaling tends to promote cell migration and metastasis, along with cell survival mechanisms, 25 more recent reports have also shown that this kinase can mediate breast cancer cell death. 2628 …”
Section: Introductionmentioning
confidence: 99%
“…Of importance, oxidative stress can trigger caspase 2 activation [18, 20, 21]. Nitric oxide (NO) production through up-regulation of inducible nitric oxide synthase (iNOS) can also be a potential target of JNK signaling [22, 23]. Increased nitric oxide (NO) production, through upregulation of iNOS, has also been implicated in cellular injury and apoptosis in a variety of cell systems, including hepatocytes [22, 23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide (NO) production through up-regulation of inducible nitric oxide synthase (iNOS) can also be a potential target of JNK signaling [22, 23]. Increased nitric oxide (NO) production, through upregulation of iNOS, has also been implicated in cellular injury and apoptosis in a variety of cell systems, including hepatocytes [22, 23, 24]. One possible mechanism by which NO can induce apoptosis is through perturbation of the BAX/BCL2 rheostat and the subsequent activation of the mitochondria-dependent death pathway [22, 24].…”
Section: Introductionmentioning
confidence: 99%